Agenda Building Agenda Media Atribut Politik melalui Press Release dan Pemberitaan Koran - Parinussa, Birgitta Femylia E.; Hartiana, Theresia Intan; Nugraheni, Yuli (Jurnal Studi Komunikasi, 2021)
The research aims to analyse the agenda building by political Public Relations of the presidential candidates through press releases and how newspapers highlight it. This is a descriptive quantitative research using content analysis methods. The results of this study indicate that the political Public Relations of the Presidential candidates has well implemented the information subsidies in their press releases.